Redes de interações tróficas no reservatório de Segredo e um tributário do rio Iguaçu, bacia do rio Iguaçu, Paraná, Brasil (1994-1996). - Abes, Sara da Silva (2003)
Two trophic steady state models (second and third periods) were elaborated for the Segredo Reservoir and the Iratim River, using the Ecopath II software. Segredo Reservoir, the second of a cascade of four reservoirs in the Iguaçu River, was closed in 1992. Iratim River is the largest tributary of the Segredo Reservoir. The diagram flows of the Segredo Reservoir show two trophic groups of the fish (carcinófagos and malacófagos) that are not included in models of the Iratim River. Among other features of food webs, the summary of statistics showed that Segredo Reservoir is a system of intermediary development, which should be reaching a level of stability. Moreover, the Iratim River may be classified as relatively developed and mature system. The detritus (from the drowning of the vegetation) seem to key to the flow of energy in the reservoir trophic networks, in their first years after impoundment, supporting the trophic structure of the ecosystem. The detritus seems to exert similar function in the Iratim River. However, specific studies are needed on the autochthonous and allochthonous detritus. Future projects for the prediction of effects of management strategies for these areas altered by impoundment, should include simulations, requiring a series of static models for this purpose. These models should include the tributary connected to these dam areas.